Indonesian EFL Students' Perspective on Free4Talk: A Novice vs. Expert User Study - Sitanggang, Cansa Namira; Maslathif Dwi Purnomo (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study investigates the perceptions of final-year English major students toward the Free4Talk platform by comparing novice and expert users. A total of 15 participants were purposively selected from a public university in North Sumatra, Indonesia, comprising 12 novice users (with less than three months of experience) and 3 expert users (with more than one year of experience). Adopting a qualitative descriptive-comparative design, data were collected through questionnaires from all participants and interviews with eight volunteers. Thematic analysis was applied to interpret the data. Findings reveal that both groups perceived Free4Talk positively, particularly for its accessibility, discussion rooms, and opportunities for authentic speaking practice. Novice users frequently encountered initial anxiety, challenges in comprehending various accents, and inconsistent motivation, whereas expert users exhibited greater confidence, consistent engagement, and long-term motivation. Both groups shared common challenges related to technical issues and limited content moderation. The study highlights that user experience, affective readiness, and prior familiarity with the platform significantly impact engagement, confidence, and speaking development, offering practical insights for online speaking platforms and English language instruction.